Preparation, Characterization, and In Vitro Hemocompatibility of Glutaraldehyde-Crosslinked Chitosan/Carboxymethylcellulose as Hemodialysis Membrane - Khabibi Khabibi; Dwi Siswanta; Mudasir Mudasir (Indonesian Journal of Chemistry, 2021)
This study aims to examine the manufacture, characterization, and in vitro hemocompatibility of glutaraldehyde-crosslinked chitosan/carboxymethyl cellulose (CS/CMC-GA) as a hemodialysis membrane. The CS/CMC-GA membrane was prepared using the phase inversion method with 1.5% CS and 0.1% CMC. The chitosan was crosslinked with glutaraldehyde in various monomers ratios, and the membranes formed were characterized by FTIR, SEM, and TGA. Furthermore, the hydrophilicity, swelling, porosity, mechanical strength, and dialysis performance of the membranes against urea and creatinine were systematically examined, and their in-vitro hemocompatibility tests were also conducted. The results showed that the CS/CMC-GA membranes have higher hydrophilicity, swelling, porosity, mechanical strength, and better dialysis performance against urea and creatinine than chitosan without modification. In addition, the hemocompatibility test indicated that the CS/CMC-GA membranes have lower values of protein adsorption, thrombocyte attachment, hemolysis ratio, and partial thromboplastin time (PTT) than that of pristine chitosan. Based on these results, the CC/CMC-GA membranes have better hemocompatibility and the potential to be used as hemodialysis membranes.